Peran Mutual Legal Assistance Dalam Memerangi Kejahatan Transnasional Penangkapan Ikan Secara Ilegal di Indonesia - Manurung, Karina Hasiyanni; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Illegal fishing is an issue that has a broad and serious impact on the economy, environment and maritime security. First of all, this illegal practice causes significant economic losses for Indonesia, estimated at hundreds of trillions of rupiah every year. Apart from that, illegal fishing also has a serious impact on marine ecosystems and the sustainability of fisheries resources. The research method used is normative research. This research aims to analyze and test the application of norms contained in legal regulations, such as laws and other legal literature, which are related to the main issues discussed. The problem approach is used to identify and limit research problems, so that the process of data collection, analysis and discussion becomes more structured and focused. The research results show that Mutual Legal Assistance (MLA) has a crucial role in fighting transnational crime, especially illegal fishing (IUU Fishing) in Indonesia. MLA enables effective international cooperation, facilitating the exchange of information, evidence collection, and cross-border legal action. The types of assistance that can be sought through MLA, such as locating and identifying individuals, obtaining evidence, and seeking the appearance of witnesses in court, have proven to be very important in supporting law enforcement in the fisheries sector. The implementation of regulations such as Law Number 45 of 2009 concerning Fisheries and Law Number 1 of 2006 concerning Mutual Assistance in Criminal Matters, as well as relevant international legal principles, shows that existing regulations are adequate to deal with IUU Fishing.